Development of the Brazilian Anti Schistosomiasis Vaccine Based on the Recombinant Fatty Acid Binding Protein Sm14 Plus GLA-SE Adjuvant - Tendler, Miriam; Almeida, Marilia; Simpson, Andrew (Frontiers in Immunology, 2015)
Data herein reported and discussed refer to vaccination with the recombinant Fatty Acid Binding protein family member of the Schistosomes, called Sm14, discovered and developed under a Brazilian platform leaded by the Oswaldo Cruz Foundation, from the Health Ministry in Brazil, undertaken to assess safety and immunogenicity in healthy volunteers. This paper reviews past and recent outcomes of developmental phases of the Sm14 based anti Schistosomiasis vaccine addressed to, ultimately, impact transmission of the second most prevalent parasitic endemic disease worldwide.